Three-Dimensional Printing/Bioprinting and Cellular Therapies for Regenerative Medicine: Current Advances - Ana Catarina Sousa; Rui Alvites; Bruna Lopes; Patrícia Sousa; Alícia Moreira; André Coelho; José Domingos Santos; Luís Atayde; Nuno Alves; Ana Colette Maurício (Journal of Functional Biomaterials, 2025)
The application of three-dimensional (3D) printing/bioprinting technologies and cell therapies has garnered significant attention due to their potential in the field of regenerative medicine. This paper aims to provide a comprehensive overview of 3D printing/bioprinting technology and cell therapies, highlighting their results in diverse medical applications, while also discussing the capabilities and limitations of their combined use. The synergistic combination of 3D printing and cellular therapies has been recognised as a promising and innovative approach, and it is expected that these technologies will progressively assume a crucial role in the treatment of various diseases and conditions in the foreseeable future. This review concludes with a forward-looking perspective on the future impact of these technologies, highlighting their potential to revolutionize regenerative medicine through enhanced tissue repair and organ replacement strategies.